Interactions Between Gas Slug Ascent and Exchange Flow in the Conduit of Persistently Active Volcanoes. Issue 9 (29th August 2021) - Qin, Zhipeng; Beckett, Frances M.; Rust, Alison C.; Suckale, Jenny
Abstract: Many volcanoes around the world are persistently active with continuous degassing for years or even centuries, sometimes exceeding historic records. Such long‐term stability contrasts with short‐term instability, reflected in eruptive episodes that punctuate passive degassing. These two aspects of persistent activity, long‐term stability as opposed to short‐term instability, are often conceptualized through two distinct model frameworks: Exchange‐flow in volcanic conduits is commonly invoked to explain the long‐term thermal balance and sustained passive degassing, while the ascent of large gas slugs is called upon to understand explosive eruptions. While typically considered separately, we propose here that both flow processes could occur jointly in the conduits of persistently active volcanoes and in transient connections between subvolcanic melt lenses. To understand the dynamic interplay between exchange flow and slug ascent, we link analogue laboratory experiments with direct numerical simulations. We find that the two flows superimpose without creating major disruptions when only considering the ascent of a single gas slug. However, the sequential ascent of multiple gas slugs is disruptive to the ambient exchange flow, because it may entail continual buildup of buoyant magma at depth. While our study focuses on the laboratory scale, we propose that the dependence of exchange‐flow stability on sequential slug ascent is relevant for understanding why explosive sequences are sometimes followed by effusive eruptions. Taken together, our work suggests that integrating exchange flow and slug ascent could provide a more complete understanding of persistently active volcanoes than either model framework offers in isolation. Plain Language Summary: Many volcanoes around the world erupt frequently, some of them on a daily basis, emitting large quantities of gas, but erupting relatively little magma. Gas fluxes remain high even when there is no eruptive activity, suggesting that magma acts as a conveyer belt that transports gas bubbles to the surface and returns to depth degassed, having lost its buoyant cargo. The framework quantifying this process is called the exchange‐flow model. It explains observations of high heat and gas flux, but raises a new question: If gas transport is efficient enough to allow continuous gas emission without eruptive activity, why does not all of the gas escape in this way? One possibility is that gas accumulates into large bubbles that exceed the capacity of the magmatic conveyer belt and rise to the surface by themselves, expanding and accelerating on the way. The framework quantifying this process is called the slug model. Here, we integrate these two models by studying their interactions in laboratory experiments and computer simulations. We find that one can impede the functionality of the other, which could be relevant for transitions in eruptive regimes, such as a switch from episodic explosions to outpourings of magma. Key Points: Experiments and simulations demonstrate the value of coupling slug ascent and exchange flow in models of persistently active volcanoes A single slug can pass through an exchange flow without creating a lasting disruption because it ascends much faster than the core magma Sequential slug ascent disrupts the mass balance of the exchange flow, potentially contributing to transitions in eruptive regimes